Quality of Kefir Combination Between Soy Milk and Skim Milk On Variation of Sugar and Fermentation Duration - Uswatiningtyas, Masithoh; Suryani, Titik (Universitas Muhammadiyah Surakarta, 2023)
Kefir is one of the functional beverages that has an acidic taste due to the activity of lactic acid during the fermentation process. One of the ingredient innovations for kefir was soy milk, skim milk and variations of sugar types. Soy milk protein has an amino acid structure similar to cow's milk, so it is very good for people with lactose intolerance. The aim of this study is to know the quality (total of lactic acid and the organoleptic quality) of the kefir combination between soy milk and skim milk on the variation of sugar and fermentation duration. The study used experimental methods and complete random design (CRD) with two factors. Factor I was the sugar variation (N) palm sugar and white sugar. Factor II was the variation of fermentation duration (K) 24 hours, 36 hours, and 48 hours. The results of the study showed that the lowest lactic acid of kefir combination between soy milk and skim milk was 0.896 % on N2K1 treatment (white sugar + 24-hour fermentation duration). The best organoleptic quality of kefir combination between soy milk and skim milk was N2K1 white sugar + 24-hour fermentation duration) in white color, sour taste, and soft texture.